7 - Power-sharing and Conflict Management in Africa: Nigeria, Sudan and Rwanda: 10.4314/ad.v25i3.22107 - Akinyele, R.T. (Africa Development, 2000)
The nature of conflicts in Africa has continued to attract the attention of scholars. This is largely because most of the violent conflicts currently witnessed in the world are taking place on the continent. This article attributes the ethnic character of most of the conflicts to the capacity of ethnicity to modify or feed on other forms of conflicts. Using Nigeria, Sudan and Rwanda as case studies, the article proposes the adoption of Rotational Presidency and the Zoning of important State offices as a solution to the fear of sectional domination which is at the centre of many conflicts